2016
DOI: 10.1016/j.crci.2016.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of South African coal fly ash into ZSM-5 zeolite and its application as an MTO catalyst

Abstract: This study presents a way of using South African coal fly ash by extracting metals such as Al and Fe with concentrated sulphuric acid, and then using the solid residue as a feedstock for the synthesis of ZSM-5 zeolite. The percentage of aluminium and iron oxides decreased from 28.0 ± 0.2% and 5.0 ± 0.1% in coal fly ash to 24.6 ± 0.1% and 1.6 ± 0.01% in the acid treated coal fly ash respectively. The fly ash-based zeolite ZSM-5 sample synthesised from the solid residue after extraction of Al and Fe, contained 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…Several routes to prepare various zeolite types have been suggested based on the pre-treatment of the fly ash, alkalinity of the hydrothermal solution, molarity of alkaline agents, solution/solid ratio, templating agent, time, temperature and time of incubation [2][3][4][5][6][7][8][9]. ZSM-5 is synthesized from a hydrothermal solution containing Al and Si sources, a mineralizing agent (OH − or F − ) and an organic structure-directing agent (OSDA) [10][11][12][13], with tetrapropylammonium cation (TPA + ) being the most-used OSDA [9,[14][15][16]. The OSDAs that give pure ZSM-5 increase as follows: alcohols < amines < tetrapropylammonium halide.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several routes to prepare various zeolite types have been suggested based on the pre-treatment of the fly ash, alkalinity of the hydrothermal solution, molarity of alkaline agents, solution/solid ratio, templating agent, time, temperature and time of incubation [2][3][4][5][6][7][8][9]. ZSM-5 is synthesized from a hydrothermal solution containing Al and Si sources, a mineralizing agent (OH − or F − ) and an organic structure-directing agent (OSDA) [10][11][12][13], with tetrapropylammonium cation (TPA + ) being the most-used OSDA [9,[14][15][16]. The OSDAs that give pure ZSM-5 increase as follows: alcohols < amines < tetrapropylammonium halide.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that ZSM-5 zeolite can be synthesized from fly ash. In most cases, a source of silica needs to be added [9,13,21,22], which does not promote the use of fly ash as feedstock in the synthesis of ZSM-5 at large scale. However, Xing and Hongyan reported the synthesis of ZSM-5 from an alkaline supernatant of a pulverized fuel ash without additional source of silicon or aluminum [23].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations